Above-barrier surface electron resonances induced by a molecular network - Stiufiuc, R.; Perdigão, L.; Grandidier, D.; Deresmes, D.; Allan, G.; Delerue, C.; Stiévenard, D.; Beton, P.; Erwin, S.; Sassi, Michel; Oison, V.; Debierre, J.-M. (American Physical Society, 2010)
We report the modification of the density of states of the Ag/Si (111)−√3×√3R30° surface by a self-assembled molecular network at energies much higher than the height of the potential barriers induced by the molecules. Map of the differential conductance obtained by scanning tunneling spectroscopy reveals an increase in the electron density in the pores of the network. This enhanced electronic resonance is explained by theoretical calculations where the periodic potential introduced by the molecular network causes band replica with an alteration of the surface band structure.